Evolution of forest systems: the role of biogeochemical cycles in determining sustainable forestry practices - Fluck, Werner Thomas (2009)
The exploitation of natural resources such as forests leads to sustainable forest management (SFM). The key question is how to define and parametrize "sustainable use." Promoting forest use that conserves spatial characteristics of forest landscapes and the structure and composition of forest stands was proposed as a way of maintaining elements of biodiversity such as species richness and genetic variation. However, to establish the parameter space for sustainable forest use, it is essential to consider the nutrient requirements of forest systems, that is, plants and animals, the need for fertilizer application, and the effects on biogeochemical cycles, a cornerstone of biological evolution and, thus, biodiversity. The use of forest products is inevitably tied to exporting biomass from those ecosystems because products are used elsewhere, thus changing natural practically steady-state ecosystems to open ones. Continued biomass export results in soil acidification and nutrient removal. Among macronutrients, phosphorus takes a key position, but several others have been shown to be depleted in managed-forest systems. Micronutrients are more crucial for forest-dwelling animals, particularly those nutrients that are only essential to animals. Depletion of their reserves, selenium for instance, through biomass export will not affect plants, and initial subclinical effects on animals are difficult to detect. The generalized effect may be reflected in changing rates of recruitment or disease resistance, and thus ecosystem processes. Forest products and their export reduces soil-nutrient reserves, and slash burning and water runoff further add to cumulative losses of several minerals. Such impacts from forest products need to be addressed, particularly for mammals and their unique needs for several microelements. Biogeochemical cycles disturbed by exporting forest products will affect plants and animals and, therefore, ecosystems and their processes, and these effects need to be incorporated in SFM designs.